An improved design of the fused silica capillary flow cell for absorbance detection in microcolumn liquid chromatography - Gogaľová, Zuzana; Kahle, Vladislav; Šesták, Jozef (Analytica chimica acta, 2023)
Efficient absorbance detection of a low-volume chromatography peak is a difficult task. In this work, an improved design of the fused silica capillary flow cell for absorbance detection in microcolumn liquid chromatography is described. The cell was fabricated from 0.15 mm I. D. fused silica capillary and silica optical fibres. Optical fibres were fully integrated into the cell design and enabled a convenient and effective connection of the cell with the light source and light detector (265 nm UV LED and photodiode in this work). Manufactured cells covered the range of physical lengths 3.1-9.9 mm (55-175 nL) and were used without any focusing optics and slits. Baseline noise was typically below 0.05 mAU and the effective optical path determined in the experiments was 83-97% of the cell's physical length. The level of stray (parasitic) light indicated by a 1% deviation from linearity at 1.7 AU was 0.08% only. The proposed cell design was found to be moderately susceptible to the refractive index change (20-35 mAU baseline change in 5-95% (v/v) gradient of acetonitrile or methanol in a mixture with water, G index up to 4 AU·s/RIU). Manufactured cells were finally applied for absorbance detection of components of test the mixture eluted off 0.3 mm I. D. microcolumn. 9.9 mm cell (175 nL) with an effective optical path of 8.9 mm exhibited contribution to the broadening of chromatography peak comparable with commercial 6 mm (80 nL) rectangular flow cell.
Keywords: Optical fibre; Optical Fibers; voda; oxid křemičitý; Chromatography, Liquid; obchod; Commerce; Silicon Dioxide; optická vlákna; Stray light; Millimetre-scale optical path; Microcolumn liquid chromatography; Water; Miniaturized detection cell; chromatografie kapalinová; Absorption photometry